Pengaruh Morfometri DAS terhadap Debit dan Sedimentasi DAS Yeh Ho - I DEWA PUTU GDE ABIJANA DHARMANANTA; R. SUYARTO; NI MADE TRIGUNASIH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Impact of Watershed Morphometric to Debit and Suspended Load of Yeh Ho Watershed Watershed (DAS) is a land area which is a unity with the river and its tributaries, which functions to accommodate, store and drain water. Morphometryand physical properties of the watershed give effect to changes in discharge and river sediment content. With the aim of knowing the effect of water level on Yeh Ho watershed discharge and sedimentation and the correlation between morphometry and the physical condition of the watershed by ratting curve discharge and sediment content. This research was conducted in the Yeh Ho river flow area in Tabanan Regency from November - February 2018 with methods: (1) literature study, (2) analysis of satellite imagery with the world view image of the 2013-2015 observation year, (3) analysis of regional characteristics river flow using DEM imagery (digital elevation mode), (4) debit analysis and (5) analysis of sediment content. The results of the DEM analysis determine the characteristics and watershed boundaries which are then analyzed to produce morphometry and physical properties of the watershedwith data sources from (BAPPEDA Tabanan Regency). The results of the analysis show that the water level has an effect of 97% on the discharge and sedimentcontent. The correlation of morphometry and physical condition of watershed with ratting curve discharge and sediment content was expressed in morphometric scores of 120 (Good watershed conditions) and physical conditions in good and very good categories.